River-sea transitions of sediment dynamics: A case study of the tide-impacted Yangtze River estuary. (5th September 2017) - Yang, H.F.; Yang, S.L.; Xu, K.H.
Abstract: Hydrodynamics and sediment dynamics vary greatly in tide-dominated estuaries worldwide, but there is a paucity of data of large tide-dominated estuary systems due to difficulties of observation in a large spatial scale. In this study, we investigate sediment dynamic transitions in a 660-km long section between the tidal limit and mouth of the Yangtze River. We found that tidal effects are almost undetectable in the uppermost 100-km section, but the mean tidal range gradually increases downstream to nearly 3 m at the river mouth. Flow is generally unidirectional in the uppermost 400-km section, although its velocity changes in response to flood/ebb tidal dynamics; in the lowest 250-km section, flow is bidirectional, and ebb flow durations decrease towards the sea. In the lowermost 100 km, the ebb flow durations decreases to below 60%, and the flow is dominated by tidal currents. Salinity is only detectable in the lowest 100-km section due to the dominance of Yangtze River water discharge. Bed sediments mainly include sand in the uppermost 500-km section, whereas mud dominates in the remaining areas. In contrast, the median grain size of the suspended sediments was found to be greater in the lowest 100-km section (8–13 μm) than in the upper sections (5–6 μm) due to strong exchanges between suspended and near bed sediments. The suspended sediment concentration (SSC) was found to be low (<0.1 g/L) and homogenous in the uppermost 100-km section, downstream of which the SSC increased rapidly to >1 g/L and both surface-bottom and intratidal variabilities occurred. The rates of sediment parameter changes were rapid in the river-sea transitional zone, and this zone may shift upstream and downstream in response to the relative contributions of the river, tides and waves. A conceptual model of the river-sea transition of sediment dynamics for the Yangtze estuary was established, and this model shed light on quantitative studies of sediment dynamics in other large tide-impacted estuaries worldwide.